From Efficiency to Care: Shifting Accountabilities in COVID-19 Digital Job Placement - Flügge, Asbjørn William Ammitzbøll; Møller, Naja Holten (2020)
ABSTRACT Large parts of society closed down in response to the COVID-19 pandemic, which transformed the provision of government services including welfare. In Denmark, employment assistance efforts at job centers were suspended between March 12 – May 15, 2020. Here caseworkers assessed individuals’ need for welfare remotely instead of physical interviews at the job center. We conducted weekly interviews with 6 job consultants across 3 Danish job centers over ten weeks to understand how their work practices changed during the pandemic (> 60 interviews). We identify a shift in the logic of casework from efficiency towards care, as the data infrastructure for approving welfare to unemployed individuals, broke down. The shift to remote job placement was both fully digital but at the same time relying on caseworkers patching the data infrastructure (e.g. relying on communication by telephone to reach job seekers). The paper contributes a unique understanding of the underlying assumptions of the model of work in caseworker systems. In the wake of the pandemic, the importance of care for the individual became the predominant logic in job placement. In particular, our findings suggest that the care concept takes on different forms under the condition of “digital” remote job placement. CCS Concepts: • Human-centered computing → Human computer interactions (HCI) → Empirical studies in HCI Keywords Public services, future of work, job placement, infrastructure ABOUT THE AUTHOR/S Asbjørn William Ammitzbøll Flügge University of Copenhagen awaf@di.ku.dk Asbjørn Ammitzbøll Flügge is a PhD fellow researching algorithms and decision-making in public services. Naja Holten Møller University of Copenhagen naja@di.ku.dk Naja Holten Møller is an assistant professor researching data-driven technologies, data-tracking, casework-citizen interaction. Both are employed at a part of the Software, Data, People and Society research section and the Confronting Data Co-Lab at Dep. of Computer Science at University of Copenhagen. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).